Effect of Subculture Frequency Toward Growth And Carotenoid Content from Tomato (Lycopersicon Esculentum Mill.) Callus - Reni Indriani; Erma Prihastanti; Rini Budihastuti; Yulita Nurchayati (Jurnal Biodjati, 2020)
Tomatoes (Lycopersicon esculentum Mill.) are a source of carotenoids they are easy to find. These compounds function as precursors of vitamin A, antioxidant, and prevent cancer. The extraction of carotenoid compounds for commercial products usually uses fresh plants, which are less efficient and require a lot of raw materials. The supply of these raw materials can be done through tissue culture. The frequency of subculture or supply of nutrients in tissue culture is very influential on the content of callus carotenoids produced. This study aimed to determine the effect of subculture frequency on growth, development and callus carotenoid content and to find out the right frequency of subculture to produce callus with optimal growth, development and carotenoid content. The design this study was a single Completely Randomized Design (CRD) with 4 treatments of subculture frequency and 5 replications. The data obtained were analyzed by ANOVA at the 95% test level followed by DMRT in case a significant different was found The results showed subculture frequency affected growth, development and carotenoid content of callus Lycopersicon esculentum. Mill. The most optimal treatment to induce growth and production of carotenoids in this study was treatment of thrice subculture while the most optimal treatment in inducing development was the twice subculture treatment.